Tarian Bonet sebagai locus theologicus: Inkulturasi kasih persaudaraan 1 Petrus 3:8 dalam tradisi Atoni Pah Meto - Junior Natan Silalahi; Fenieli Harefa; Odaligo Zai (KURIOS, 2026)
This study examines the Bonet Dance of the Atoni Pah Meto community in East Nusa Tenggara as a locus theologicus through which the theological teaching of brotherly love in 1 Peter 3:8 is interpreted and embodied contextually. Employing qualitative ethnographic methods combined with a grammatical-historical exegetical approach, data were collected through participant observation and in-depth interviews with community informants in Timor Tengah Selatan. Thematic analysis following the framework of Braun and Clarke was applied to interpret the findings. The study demonstrates that the five ethical qualities in 1 Peter 3:8, namely unity of mind (homophrones), sympathy (sympatheis), brotherly love (philadelphoi), compassion (eusplanchnoi), and humility (tapeinophrones), resonate substantively in the symbolic vocabulary, formational logic, and communal ethos of the Bonet Dance. The study also critically examines the tensions inherent in the process of inculturating Christian values into a cultural tradition that predates Christianization. Drawing on Bevans' synthesis model of contextual theology, the research argues that Bonet constitutes an authentic locus of theological reflection within the Christian community of Atoni Pah Meto and offers a replicable model of inculturation for Indonesian contextual theology.   Abstrak  Penelitian ini mengkaji Tarian Bonet dalam masyarakat Atoni Pah Meto, Nusa Tenggara Timur, sebagai locus theologicus ajaran kasih persaudaraan dalam 1 Petrus 3:8, yang diinterpretasikan dan dihayati secara kontekstual. Menggunakan metode etnografi kualitatif yang dipadukan dengan eksegesis gramatikal-historis, data dikumpulkan melalui observasi partisipatif dan wawancara mendalam dengan informan dari komunitas di Timor Tengah Selatan. Analisis tematik mengacu pada kerangka Braun dan Clarke yang diterapkan untuk menginterpretasikan temuan. Hasil penelitian menunjukkan bahwa kelima kualitas etis dalam 1 Petrus 3:8: kesatuan pikiran (homophrones), seperasaan (sympatheis), kasih persaudaraan (philadelphoi), penyayang (eusplanchnoi), dan rendah hati (tapeinophrones) memiliki resonansi substantif dalam kosakata simbolik, logika formasi, dan etos komunal Tarian Bonet. Penelitian ini juga menelaah secara kritis ketegangan yang inheren dalam proses inkulturasi nilai-nilai Kristen ke dalam tradisi budaya yang telah mendahului Kristenisasi. Mengacu pada model sintesis Bevans dalam teologi kontekstual, penelitian ini berargumen bahwa Bonet merupakan locus teologis yang autentik dalam kehidupan komunitas Kristen Atoni Pah Meto dan menawarkan model inkulturasi yang dapat direplikasi bagi teologi kontekstual Indonesia.